2023
DOI: 10.1177/17590914231198980
|View full text |Cite
|
Sign up to set email alerts
|

An Association of Chitinase-3 Like-Protein-1 With Neuronal Deterioration in Multiple Sclerosis

Intakhar Ahmad,
Stig Wergeland,
Eystein Oveland
et al.

Abstract: Elevated levels of Chitinase-3-like protein-1 (CHI3L1) in cerebrospinal fluid have previously been linked to inflammatory activity and disease progression in multiple sclerosis (MS) patients. This study aimed to investigate the presence of CHI3L1 in the brains of MS patients and in the cuprizone model in mice (CPZ), a model of toxic/metabolic demyelination and remyelination in different brain areas. In MS gray matter (GM), CHI3L1 was detected primarily in astrocytes and in a subset of pyramidal neurons. In neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In 2010, Comabella et al identified that CHI3L1 seems to be a prognostic biomarker for conversion to MS and development of disability utilizing the previously collected cerebrospinal fluid samples from MS patients by a mass spectrometry-based proteomic approach validating with ELISA (enzyme-linked immunosorbent assay) [75]. Positively associated elevation of CHI3L1 in MS samples was followed/reviewed by many other groups so far [27][28][29][30][31][32][33][34][35][76][77][78].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, Comabella et al identified that CHI3L1 seems to be a prognostic biomarker for conversion to MS and development of disability utilizing the previously collected cerebrospinal fluid samples from MS patients by a mass spectrometry-based proteomic approach validating with ELISA (enzyme-linked immunosorbent assay) [75]. Positively associated elevation of CHI3L1 in MS samples was followed/reviewed by many other groups so far [27][28][29][30][31][32][33][34][35][76][77][78].…”
Section: Multiple Sclerosis (Ms)mentioning
confidence: 99%
“…[ [27][28][29][30][31][32][33][34][35] Neuron (AD) 1 ⃝ 4 ⃝ CSF (<5 folds in adults), Tissue(<10 folds ↑in adults)…”
mentioning
confidence: 99%